Estrogens and development. - McLachlan, J A (1987)
The normal development of the genital organs of mammals, including humans, is under hormonal control. A role for the female sex hormone estrogen in this process is still unclear. However, exposure of experimental animals or humans to the potent exogenous estrogen, diethylstilbestrol (DES), results in persistent differentiation effects. Since many chemicals in the environment are weakly estrogenic, the possibility of hormonally altered differentiation must be considered.